Maghrebian Entrepreneurs in Quebec:: An Exploratory Study and a Conceptual Framework - Allali, Brahim (Journal of Comparative International Management, 2010)
The Maghrebian community is becoming the most important and the fastest growing ethnic group in Quebec, Canada. Despite their obvious assets such as a high level of education and sound experience, its members still face the greatest difficulties finding a convenient job. No wonder Maghrebian immigrants are among the poorest of the province according to informal statistics by the community leaders. To overcome this "social disadvantage", many Maghrebian immigrants choose to start a business; other alternatives being going back home, moving to another Canadian province or even another country, and applying for the government social welfare program. The major aim of this exploratory paper is to identif the most important conditions under which Maghrebian entrepreneurs start their businesses in Quebec.